Safety and quality issues in summer squashes using handheld portable NIRS sensors for real‐time decision making and for on‐vine monitoring. (9th September 2019) - Entrenas, José‐Antonio; Pérez‐Marín, Dolores; Torres, Irina; Garrido‐Varo, Ana; Sánchez, María‐Teresa
Abstract: BACKGROUND: Portable handheld near infrared spectroscopy (NIRS) instruments currently present enormous advantages in terms of size, weight, and robustness. They also provide fast, precise information that can be obtained in situ, and they represent a viable option for controlling vegetable safety and quality during the growth period. The aim of this research was to evaluate three handheld portable NIRS instruments for in situ and real‐time analysis of intact summer squashes. Traditional methods were used to analyze 221 summer squashes, and this work was used to develop calibration models for morphological, safety, and quality parameters. The longitudinal distribution of nitrate content in summer squashes weighing over 400 g was also studied, and the evolution of this parameter during the harvest period was tracked to determine which summer squashes and which zones of the vegetables (peduncle, equatorial, or stylar) could be earmarked for baby‐food production. RESULTS: The robustness of the calibration models confirmed the expectations raised by NIRS technology for morphological, safety, and quality control of individual summer squashes, and the models developed with the MicroNIR‐1700 instrument were those that provided more accuracy and precision, being the peduncle zone the part with higher nitrate content. CONCLUSIONS: It is in the peduncle zone, therefore, where measurements of this parameter must be carried out to decide on the destination of the harvested product. Summer squashes picked at the end of the harvest are those that must be used for baby‐food production. © 2019 Society of Chemical Industry